2016
DOI: 10.1161/circresaha.115.308093
|View full text |Cite
|
Sign up to set email alerts
|

Individual Cardiac Mitochondria Undergo Rare Transient Permeability Transition Pore Openings

Abstract: Rationale Mitochondria produce ATP, especially critical for survival of highly aerobic cells such as cardiac myocytes. Conversely, opening of mitochondrial high-conductance and long-lasting permeability transition pores (mPTP) causes respiratory uncoupling, mitochondrial injury and cell death. However, low-conductance and transient mPTP openings (tPTP) might limit mitochondrial Ca2+ load and be cardioprotective, but direct evidence for tPTP in cells is limited. Objective To directly characterize tPTP occurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
87
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(91 citation statements)
references
References 37 publications
2
87
2
Order By: Relevance
“…Interestingly, these transient openings operate at a subconductance state and appear to allow solutes no larger than 300–600 Daltons to pass. The different modes of opening could provide a means for selective signaling and indicate that transient openings could be a result from lower oligomerization configurations of the pore (Ichas et al 1997; Lu et al 2015). …”
Section: Characteristics Of the Mptpmentioning
confidence: 99%
“…Interestingly, these transient openings operate at a subconductance state and appear to allow solutes no larger than 300–600 Daltons to pass. The different modes of opening could provide a means for selective signaling and indicate that transient openings could be a result from lower oligomerization configurations of the pore (Ichas et al 1997; Lu et al 2015). …”
Section: Characteristics Of the Mptpmentioning
confidence: 99%
“…The molecular composition of the MPTP is not established and still a matter of debate. Recently, literature has shown that few components are essential for MPTP formation such as F O F 1 ATP synthase dimmers and cyclophilin D and a transient mode has also been proposed [53]. But the unsolved question is how sex hormones affect MPTP formation?…”
Section: Discussionmentioning
confidence: 99%
“…As calcium and ROS are postulated to increase the probability of the opening of the PTP, strategies that reduce ROS and lower mitochondrial calcium overload have been extensively explored as cardioprotective interventions 25,27 . Paradoxically, transient PTP opening seems to reduce mitochondrial calcium overload, analogous to a ‘pressure release valve’, whereby mitochondrial calcium decreases upon transient PTP opening 112 . This mechanism works to reset mitochondrial calcium concentration, and is postulated to prevent the sustained, large conductance, open conformation of PTP that is associated with pathological injury and cell death.…”
Section: Targeting the Mitochondriamentioning
confidence: 99%